Management of urethral caruncle – A systematic review of the current literature. (May 2020) - Verma, Vandna; Pradhan, Ashish
Abstract: Urethral caruncle is a benign fleshy outgrowth at the urethral meatus that occurs mainly at posterior lip of urethra and is most commonly seen in postmenopausal women. They are typically asymptomatic and are mostly reported as incidental findings during pelvic examination. When symptomatic, they commonly present with bleeding, haematuria, pain, dysuria or a lump. Despite being a recognised condition in medicine for more than two centuries, urethral caruncle is still a very poorly understood condition and the current literature is largely deficient to guide the general practitioners and gynaecologists in the appropriate management of the condition. The aim of the paper is to systematically review the current literature on the management options available for urethral caruncle and highlight the need for high quality research to develop better management strategies for this condition. We searched the following electronic databases from 1946 until January 2019: MEDLINE, EMBASE, COCHRANE and WEB OF SCIENCE. The search identified a total of 41 articles on the treatment of the condition in pre- and postmenopausal women, out of which only eight studies were relevant for our review. Most of these studies were retrospective case series or small cohort studies, mainly on the surgical treatment of the lesion. We found no systematic studies in the current literature on the conservative management of urethral caruncles. The most common method of surgical treatment encountered in these studies was simple excision. In conclusion, the current literature is largely deficient to guide us in the appropriate management of this common condition and there is need for more robust studies to develop evidence based management of this distressing condition that can guide the general practitioners and gynaecologists.